(untitled) (translation. a transdisciplinary journal, 2022)
The practice of translation has always been described in metaphorical terms, as ‘fidelity’ or ‘license’, notably, and this tendency to describe it solely in terms of what it is not (to borrow Aristotle’s description of metaphor) means that as a result it is therefore always running away from itself, while its content remains unspecified.